The Effect Of Educational Exercises Using Triple Peer Education Strategy In Learning Handstand In Artistic Gymnastics - Rahim, Mohammed (Journal of Physical Education, 2017)
The aim of the study was to prepare educational exercises using Triple peer education strategy to learn the handstand technique. The researcher assumed that there are significant differences between the means of the experimental and control groups in the results of pre and posttests. The researcher used the experimental method to achieve the objectives of the study. The subjects were (30) students. The researcher concluded that the educational exercises using the triple peer education strategy have a positive effect in the learning skill of handstand.